2012
DOI: 10.5120/8410-2047
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Evolution of Architecture and Connection Weights in Artificial Neural Network

Abstract: The important issue for Designing architecture isthe evolution of Artificial Neural Network (ANN). There is no systematic method to design a near-optimal architecture for a given application or task. The pattern classification methods are used to design the neural network architectures and efforts towards the automatic design of network topologies, constructive and destructive algorithms can be used. In the proposed work the optimization of architectures and connection weights uses the evolutionary process. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Sagar et al [16] systematically suggested a way to the neural network, which has been measured for adaptive technique that increasingly self-organizes to approximate the solution, creating the situation to solve of the need as well as decidedly specify the actual methods headed for the solution. Moreover, with unnatural neural network, evolutionary computation may very well be included in order to increase the actual performance by various amounts, and consequently this kind of neural network is named as evolutionary ANN.…”
Section: Related Workmentioning
confidence: 99%
“…Sagar et al [16] systematically suggested a way to the neural network, which has been measured for adaptive technique that increasingly self-organizes to approximate the solution, creating the situation to solve of the need as well as decidedly specify the actual methods headed for the solution. Moreover, with unnatural neural network, evolutionary computation may very well be included in order to increase the actual performance by various amounts, and consequently this kind of neural network is named as evolutionary ANN.…”
Section: Related Workmentioning
confidence: 99%